Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To complete the table for the function \( f(x) = \sqrt{x+3} + 4 \), let's evaluate the function at each given \( x \) value step-by-step.
1. For \( x = -3 \):
[tex]\[ f(-3) = \sqrt{-3 + 3} + 4 = \sqrt{0} + 4 = 0 + 4 = 4 \][/tex]
2. For \( x = -2 \):
[tex]\[ f(-2) = \sqrt{-2 + 3} + 4 = \sqrt{1} + 4 = 1 + 4 = 5 \][/tex]
3. For \( x = 1 \):
[tex]\[ f(1) = \sqrt{1 + 3} + 4 = \sqrt{4} + 4 = 2 + 4 = 6 \][/tex]
4. For \( x = 6 \):
[tex]\[ f(6) = \sqrt{6 + 3} + 4 = \sqrt{9} + 4 = 3 + 4 = 7 \][/tex]
Now, let's fill in the completed table with the calculated \( y \)-values.
[tex]\[ \begin{array}{r|r} x & y \\ \hline -3 & 4.0 \\ -2 & 5.0 \\ 1 & 6.0 \\ 6 & 7.0 \\ \end{array} \][/tex]
1. For \( x = -3 \):
[tex]\[ f(-3) = \sqrt{-3 + 3} + 4 = \sqrt{0} + 4 = 0 + 4 = 4 \][/tex]
2. For \( x = -2 \):
[tex]\[ f(-2) = \sqrt{-2 + 3} + 4 = \sqrt{1} + 4 = 1 + 4 = 5 \][/tex]
3. For \( x = 1 \):
[tex]\[ f(1) = \sqrt{1 + 3} + 4 = \sqrt{4} + 4 = 2 + 4 = 6 \][/tex]
4. For \( x = 6 \):
[tex]\[ f(6) = \sqrt{6 + 3} + 4 = \sqrt{9} + 4 = 3 + 4 = 7 \][/tex]
Now, let's fill in the completed table with the calculated \( y \)-values.
[tex]\[ \begin{array}{r|r} x & y \\ \hline -3 & 4.0 \\ -2 & 5.0 \\ 1 & 6.0 \\ 6 & 7.0 \\ \end{array} \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.